\[\boxed{\text{314\ (314).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ y = f(x) - 2\]
\[\textbf{а)}\ \]
\[\textbf{б)}\ \]
\[\textbf{в)}\ \]
\[2)\ y = f(x) + 4\ \ \]
\[\textbf{а)}\ \]
\[\textbf{б)}\ \]
\[\textbf{в)}\ \]
\[3)\ y = f(x - 3)\]
\[\textbf{а)}\]
\[\textbf{б)}\]
\[\textbf{в)}\ \]
\[4)\ y = f(x + 1)\]
\[\textbf{а)}\]
\[\textbf{б)}\ \]
\[\textbf{в)}\]
\[5)\ y = - f(x)\]
\[\textbf{а)}\]
\[\textbf{б)}\]
\[\textbf{в)}\ \]
\(\ \)
\[6)\ y = 3 - f(x)\ \]
\[\textbf{а)}\]
\[\textbf{б)}\]
\[\textbf{в)}\ \]
\[\boxed{\text{314.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left\{ \begin{matrix} 2x + 3y > 6 \\ x > 0\ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} 3y > 6 - 2x \\ x > 0\ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} y > 2 - \frac{2}{3}x \\ x > 0\ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]
\[2)\ \left\{ \begin{matrix} y + 3 \geq 4x\ \ \ \\ 4x - y \geq - 2 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} y \geq 4x - 3 \\ 4x \geq y - 2 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} y \geq 4x - 3\ \ \ \ \ \ \ \ \\ x \geq 0,25x - 0,5 \\ \end{matrix} \right.\ \]
\[3)\ \left\{ \begin{matrix} x^{2} + y^{2} \leq 9 \\ x^{2} + y^{2} \geq 4 \\ \end{matrix} \right.\ \]
\[4)\ \left\{ \begin{matrix} x^{2} + y^{2} \leq 1 \\ y \geq 2x\ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \]